Implementation of the Tax Revenue Policy for the Acquisition of Land and Building Rights in the City of Bandung - Nagari, Muhamad Bangun; Rohayati, Yeti; Indah, Diani; Kamil, Indriyati (Universitas Pahlawan Tuanku Tambusai, 2024)
Land and Building Acquisition Tax (BPHTB) is an important component of local government revenue in Indonesia, designed to regulate the transfer of land and property rights. This study aims to examine the implementation of the BPHTB policy in Bandung, focusing on the operational framework established under Law No. 20 of 2000, which uses a self-assessment system to empower taxpayers to manage their tax obligations independently. Although intended to be efficient, its implementation faces several challenges, including reliance on intermediaries such as notaries, inaccuracies in reported data, and issues of public awareness regarding tax responsibilities. Using a qualitative approach, this study analyzes the roles of key stakeholders, including the Regional Revenue Agency (BPPD) and land deed officials (PPAT), in implementing the policy. The study highlights the importance of inter-agency collaboration and effective communication with the public to improve compliance and accuracy in tax collection. The results show that improving taxpayer education and simplifying regulations can significantly improve the self-assessment process, leading to increased revenue and better public service delivery. This study contributes to a broader understanding of tax administration in Indonesia and offers practical recommendations to improve the implementation of BPHTB.